For a “definitive/infinite” kind of writing - Albano, Adriana Helena de Oliveira (Revista de Letras, 2013)
This paper intends to study the memoirist poetics of Carlos Drummond de Andrade’s three “preface-poems” that begin, respectively, his three most characteristically memoirist books: Boitempo & A falta que ama (1968), Menino Antigo (1973) and Esquecer para lembrar (1979). The key theoretical texts used are Jacques Derrida’s fundaments on the characteristics of the autobiographical text and its ability to articulate the subject’s past experiences as a form of detachment from himself or herself in search of a self-assessment that can provide self-knowledge. We intend to enhance the “critical” field of the Itabira poet’s lyricism through this focus on writing, not to reiterate or judge his poetic assumptions, but to help reveal the constitutive dilemmas of the written experience.